Terrorism Within Comparative International Context - Haberfeld, M.R. author. aut Link
XIV, 176 p.
Keywords: The post-9/11 era, with its emphasis on preparedness against terrorist attacks, has seen an ongoing conflict of priorities between law enforcement agencies and the civilian sector: public safety versus individual rights. Community-oriented policing—mobilizing community support in partnership with local law enforcement—has been developed internationally to address this issue, and Terrorism within Comparative International Context assesses the progress and shortcomings of community-based programs. Written by leading experts in police science and based on extensive interviews and focus groups with law enforcement, media, and community representatives, the book offers: A comparative database on terror control strategies in, among others, Ireland, Turkey, Sweden, Spain, the United Kingdom and the Netherlands Analysis of the interaction between the community and local law enforcement in response to terrorist activities. Insights into the relationships between home-grown terrorists, the preventive role of the community, and the proactive role of local law enforcement. A "Best Practices" section including recommendations for investigation and interrogation techniques. A real-world template for training law enforcement personnel. Terrorism within Comparative International Context is critical reading for researchers, students and professionals across a range of interrelated fields, including criminal justice, terrorism/counterterrorism, organized crime, police science, and public administration, and makes an up-to-date textbook for courses in these areas.